2021
DOI: 10.3389/fcell.2021.619444
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Transfer of miR-185 Is Controlled by hnRNPA2B1 and Impairs Re-endothelialization After Vascular Injury

Abstract: Dysfunction of endothelial cells (ECs) contributes to restenosis after vascular reconstruction for patients with coronary artery disease (CAD). The intercellular communication between ECs and vascular smooth muscle cells (VSMCs) might be critical in the development of restenosis and can be mediated by exosomes carrying functional microRNAs. miR-185 is reported to be associated with atherosclerosis, whether it plays a similar role in restenosis is unknown. In this study, we observed an elevated level of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Our study shows that PABPC1 can increase expression of miR-21-5p, in ESCC cells, which is then encapsulated in ESCC cell-derived exosomes to target vessel endothelial cells and induce angiogenesis. Importantly, we further investigated how miR-21-5p is packaged into exosomes, showing that PABPC1 can bind miR-21-5p, through an ACUGAUG sequence, to direct miR-21-5p packaging into exosomes, similar to other studies showing involvement of other RBPs, such as hnRNPQ and hnRNPA2B1, in exosomal miRNA export [ 32 , 33 ]. Previous studies showed the pro-angiogenic properties of endogenous miR-21-5p and cancer cell derived-miR-21-5p to be dependent on KRIT1 and Spry1 in vessel endothelial cells [ 34 36 ].…”
Section: Discussionsupporting
confidence: 62%
“…Our study shows that PABPC1 can increase expression of miR-21-5p, in ESCC cells, which is then encapsulated in ESCC cell-derived exosomes to target vessel endothelial cells and induce angiogenesis. Importantly, we further investigated how miR-21-5p is packaged into exosomes, showing that PABPC1 can bind miR-21-5p, through an ACUGAUG sequence, to direct miR-21-5p packaging into exosomes, similar to other studies showing involvement of other RBPs, such as hnRNPQ and hnRNPA2B1, in exosomal miRNA export [ 32 , 33 ]. Previous studies showed the pro-angiogenic properties of endogenous miR-21-5p and cancer cell derived-miR-21-5p to be dependent on KRIT1 and Spry1 in vessel endothelial cells [ 34 36 ].…”
Section: Discussionsupporting
confidence: 62%
“…1 E, F). As described in recent research, lysoPC induces the pyroptosis of human endothelial cells by activating the NLRP3 inflammasome, which is closely related to endothelial cell dysfunction [ 23 , 27 ]. Then, the impact of GDF11 on the expression of NLRP3, Casp1 p20, IL-1β, and GSDMD-N at the protein level was further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular permeability associated with the endothelial barrier function in the aorta was determined by the procedure using Evans Blue dye 57 . One hundred μL of 1% Evans Blue dye (Nacalai Tesque) dissolved in saline was intravenously injected into mice.…”
Section: Methodsmentioning
confidence: 99%